2021
DOI: 10.1002/cncr.33777
|View full text |Cite
|
Sign up to set email alerts
|

Impact of radiation therapy facility volume on survival in patients with cancer

Abstract: Background This study examined whether radiation therapy facility volumes correlate with survival after curative intent treatment of solid tumors. Methods The National Cancer Database was queried for patients with solid tumors treated with curative‐intent radiation therapy from 2004‐2013. Facilities were stratified into 4 volume categories: low, intermediate, high, and very high. Primary cancer sites were divided into neoadjuvant, adjuvant, or definitive radiation subgroups. Kaplan‐Meier curves of 5‐year postr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 35 publications
(44 reference statements)
0
26
0
Order By: Relevance
“…Adjusted overall survival over 108 mo (continuous variable) Increasing by 100 radiation-managed patients: HR, 0.97; 95% CI, 0.95-0.98; P < .0001 2. HV vs LV facilities (categorical variable) 7-y overall survival: 76% vs 74%, P < .0005 Adjusted overall survival over 108 mo: HR, 0.91; 95% CI, 0.86-0.96, P < .0005 Patel et al; 2020 32 (USA) NCDB (n = 1899); 2004-2016 Prostate cancer; TNM stage: T1-4, N1, M0; Gleason score: 6-10 EBRT and ADT Dose ≥60 Gy (technique not specified) Age, race, tumor stage, Gleason score, PSA level, Charlson-Deyo score, percentage residence without high school degree, median income quartiles, total radiation dose, boost radiation dose, year of diagnosis, distance to facility Categorical (dichotomized): Divided at a cutoff of 67 average cumulative cases per facility per year from 2004 to the time of diagnosis for a patient HV facilities: ≥67 cases per year LV facilities: <67 cases per year Propensity-matched: yes Sensitivity analysis performed: no HV vs LV facilities: Median overall survival: 111.1 mo (95% CI, 101.5-127.9) vs 94.5 mo (95% CI, 88.2-105.8)( P = .04) 10-y overall survival: 44.7% (95% CI, 37.7%-51.6%) vs 35.6% (95% CI, 30.1%-41.1%) Adjusted overall survival over 168 mo: HR, 0.80; 95% CI, 0.67-0.99; P = .04 Tchelebi et al; 2021 28 (USA) NCDB (n = 38,296); 2004-2013 Prostate cancer; clinical disease stage I-III and unknown EBRT or BT No specific dose noted (palliative doses such as 30 Gy in 10 fractions, 20 Gy in 5 fractions, or 8 Gy in 1 fraction excluded) Age, sex, race, clinical disease stage (0, 1, 2, 3, unknown), Charlson-Deyo comorbidity score, facility type, geographic area, annual household income, surgery performed, chemotherapy, immunotherapy, distance traveled to facility Categorical (grouped): Q1: ≤3.9 cases per year (lowest volume) Q2: 3.9 to <7.2 cases per year Q3: 7.2 to <13 cases per year Q4: ≥13 cases per year (highest volume) Propensity-matched: no Sensitivity analysis performed: no Adjusted 5-y overall survival per volume quartile (reference Q1 = 1.0): Q2 vs Q1: HR, 0.97 (95% CI, 0.87-1.07; P < .51) Q3 vs Q1: HR, 0.91 (95% CI, 0.82-1.01; P < .08) Q4 vs Q1: HR, 0.82 (95% CI, 0.74-0.91; P < .001) Chen et al; 2009 33 (USA) SEER ...…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…Adjusted overall survival over 108 mo (continuous variable) Increasing by 100 radiation-managed patients: HR, 0.97; 95% CI, 0.95-0.98; P < .0001 2. HV vs LV facilities (categorical variable) 7-y overall survival: 76% vs 74%, P < .0005 Adjusted overall survival over 108 mo: HR, 0.91; 95% CI, 0.86-0.96, P < .0005 Patel et al; 2020 32 (USA) NCDB (n = 1899); 2004-2016 Prostate cancer; TNM stage: T1-4, N1, M0; Gleason score: 6-10 EBRT and ADT Dose ≥60 Gy (technique not specified) Age, race, tumor stage, Gleason score, PSA level, Charlson-Deyo score, percentage residence without high school degree, median income quartiles, total radiation dose, boost radiation dose, year of diagnosis, distance to facility Categorical (dichotomized): Divided at a cutoff of 67 average cumulative cases per facility per year from 2004 to the time of diagnosis for a patient HV facilities: ≥67 cases per year LV facilities: <67 cases per year Propensity-matched: yes Sensitivity analysis performed: no HV vs LV facilities: Median overall survival: 111.1 mo (95% CI, 101.5-127.9) vs 94.5 mo (95% CI, 88.2-105.8)( P = .04) 10-y overall survival: 44.7% (95% CI, 37.7%-51.6%) vs 35.6% (95% CI, 30.1%-41.1%) Adjusted overall survival over 168 mo: HR, 0.80; 95% CI, 0.67-0.99; P = .04 Tchelebi et al; 2021 28 (USA) NCDB (n = 38,296); 2004-2013 Prostate cancer; clinical disease stage I-III and unknown EBRT or BT No specific dose noted (palliative doses such as 30 Gy in 10 fractions, 20 Gy in 5 fractions, or 8 Gy in 1 fraction excluded) Age, sex, race, clinical disease stage (0, 1, 2, 3, unknown), Charlson-Deyo comorbidity score, facility type, geographic area, annual household income, surgery performed, chemotherapy, immunotherapy, distance traveled to facility Categorical (grouped): Q1: ≤3.9 cases per year (lowest volume) Q2: 3.9 to <7.2 cases per year Q3: 7.2 to <13 cases per year Q4: ≥13 cases per year (highest volume) Propensity-matched: no Sensitivity analysis performed: no Adjusted 5-y overall survival per volume quartile (reference Q1 = 1.0): Q2 vs Q1: HR, 0.97 (95% CI, 0.87-1.07; P < .51) Q3 vs Q1: HR, 0.91 (95% CI, 0.82-1.01; P < .08) Q4 vs Q1: HR, 0.82 (95% CI, 0.74-0.91; P < .001) Chen et al; 2009 33 (USA) SEER ...…”
Section: Methodsmentioning
confidence: 96%
“…FIGO stage IB to IIA T3 vs (T1 + T2): HR, 0.82; 95% CI, 0.61-1.10; P = .19 iv. FIGO stage IIB to IVA T3 vs (T1 + T2): HR, 0.78; 95% CI, 0.67-0.90; P < .01 Tchelebi et al; 2021 28 (USA) NCDB (n = 2788); 2004-2013 Cervical cancer; clinical disease stage I-III and unknown EBRT or BT No specific dose noted (palliative doses such as 30 Gy in 10 fractions, 20 Gy in 5 fractions, or 8 Gy in 1 fraction excluded) Age, sex, race, clinical disease stage (0, 1, 2, 3, unknown), Charlson-Deyo comorbidity score, facility type, geographic area, annual household income, surgery performed, chemotherapy, immunotherapy, distance traveled to facility Categorical (grouped): Q1: <0.4 cases per year (lowest volume) Q2: 0.4 to <0.9 cases per year Q3: 0.9 to <1.5 cases per year Q4: ≥1.5 cases per year (highest volume) Propensity-matched: no Sensitivity analysis performed: no Adjusted 5-y overall survival per volume quartile (reference Q1 = 1.0): Q2 vs Q1: HR, 0.95 (95% CI, 0.79-1.15; P < .62) Q3 vs Q1: HR, 0.92 (95% CI, 0.74-1.14; P < .43) Q4 vs Q1: HR, 0.85 (95% CI, 0.68-1.07; P < .17) Wright et al; 2015 31 (USA) NCDB (n = 12,048); 1998-2011 Cervical cancer; FIGO stage: IIB-IVA EBRT with/without CT and/or BT Dose not specified (EBRT: technique not specified) Age, race, insurance, clinical tumor grade, stage, histology, hospital region, location, type of hospital Continuous (annualized) Categorical (grouped) Total number of patients treated and divided by the number of years in which a hospital treated at least 1 patient with locally advanced cervical cancer Divided into 4 quartiles based on annualized case volumes: Q1: <2 cases per year (lowest volume) Q2: 2-3.99 cases per year Q3: 4-5.99 cases per year Q4: ≥6 cases per year (highest volume) Propensity-matched: no Sensitivity analysis performed: yes Volume effect seen on sensitivity analysis: no 1. Adjusted overall survival (continuous) variable 5-y overall survival: HR, 0.99 (95% CI, 0.98-1.00; P < .05) 2.…”
Section: Methodsmentioning
confidence: 97%
“…Hospital facilities have been shown by several groups to impact patient outcomes after cancer surgery ( 18 ). For cancers that can be treated with curative radiation therapy, treatment at a high-volume facility was associated with improved survival ( 22 ). It should be noted that cancers with the greatest benefit from high-volume facilities were those with the highest number of cancer-related deaths, including cancers of the pancreas, esophagus, and brain ( 23 ).…”
Section: Facility Type and Cancer Outcomes In The Usmentioning
confidence: 99%
“…One possible example, as suggested by SEOR is to consider a ROQI relating to RT facility volume for highly complex definitive curative intent RT, like for surgery 23 . A retrospective multivariate analysis from the American national cancer database recently showed that for certain tumour sites treated with definitive RT (Lung and head and neck cancers) this correlated with improved overall survival 39 . Therefore, should the number of cases planned per year by individual ROs or by RT provider, be included in internal standards and accreditation?…”
Section: Gaps In Roqismentioning
confidence: 99%